Estudios Locos y psicología social crítica: claves para una investigación activista en salud mental desde América Latina - Cea Madrid, Juan Carlos (Pacha. Revista de Estudios Contemporáneos del Sur Global, 2024)
The present article explores the contributions of critical social psychology and Mad Studies to think about power relations and interrogate mechanisms of domination in the field of mental health. By taking a critical stance and a committed willingness in knowledge production, the articulation of these two schools of thought allows questioning power asymmetries in research processes and sustaining new ways of understanding madness in our continent. From a Latin American perspective, it is proposed to blur disciplinary boundaries, develop alternative methodologies, and promote intersections and alliances with social struggles and movements. Around these developments, activist research is proposed as another way of generating knowledge with mad communities and promoting processes of epistemic reconstruction and emancipatory justice in contemporary mental health.